DMT-CE (Digital Media Training-Capability Enhancement) Culinary Business Sector Sop Asep Amih Sukabumi to Improve Online-Based Adaptive Marketing Capabilities - Deri Firmansyah; Asep Suryana; Asep Achmad Rifa'i; Dwinanto Priyo Susetyo (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of implementing this community service is to provide digital media training to increase the adaptability of online-based marketing by using social media applications and marketplaces that are still organic, adequate digital literacy, courage and ability for business actors to carry out digital transformation are prerequisites. important to support this goal. The implementation of the training is carried out through several stages. Through the PKM activities that have been carried out, positive information and feedback is obtained that DMT-CE is considered to be able to provide useful output that is able to motivate and encourage PKM partners, namely the Soup culinary business Mr. Asep Amih Sukabumi to be able to improve online-based adaptive marketing capabilities through the use of social media applications and marketplaces in the post-Covid-19 digital era. WhatsApp, Facebook marketplace, and IG for business are the digital platforms that are most consistently used in current digital marketing practices as a form of adoption and practice of transforming innovative and adaptive business models and processes within the digital ecosystem to rise and rise. classy, ​​has better competitiveness, and can maintain its existence by increasing profitable sales on an ongoing basis.